Case reports of incontinentia pigmenti in males - Khushboo D Gupta; Bela B Padhiar; Umesh K Karia; Bela J Shah (Wolters Kluwer Medknow Publications, 2013)
Incontinentia pigmenti is an X-linked dominant disorder, which is fatal in males, and majority of cases reported are in females. Here, we report 2 cases of males with incontinentia pigmenti. Case 1 has progressed through the classical stages of IP, giving history of vesicular and verrucous lesions and has presented with hyperpigmentation in whorled pattern. Case 2 has vesicular lesions in a linear distribution on the legs along with classical histopathological findings.